Optimal emission prices for a district heating system owner - Sebastian Wehrle; Johannes Schmidt (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2016)
Low emission prices have stirred up discussion about political measures that aim to increase emission prices. District heating system operators, often municipal utilities, use a variety of heat generation technologies that are affected by the emission trading system. We examine whether district heating system owners have an incentive to support measures that increase emission prices in the short term. Therefore, we (i) develop a simplified analytical framework to analyse optimal decisions of a district heating operator, and (ii) investigate the market-wide effects of increasing emission prices, in particular the pass-through of emission prices to power prices. Using the clustered unit commitment model MEDEA of the common Austrian and German power system, we estimate a pass-through from emission prices to power prices between 1.1 and 0.75, depending on the absolute emission price level. Under reasonable assumptions regarding heat generation technologies, the pass-through from higher emission prices to power prices is about twice as high as required to make low-emission district heating system owners better off.
Keywords: Q41; 330; Emission Price; Pass Through; Dispatch Model; District Heating; Optimization